Dampak Perubahan Iklim Terhadap Produksi Pertanian - Wahyu Muh Syata (JUMABI: Jurnal Manajemen, Akuntansi dan Bisnis, 2025)
The current climate change has the potential to significantly impact the agricultural sector, especially in agrarian countries like Indonesia. As one of the main pillars of the economy, Indonesia's agricultural sector is highly dependent on climate stability; however, threats such as changes in rainfall patterns, rising temperatures, and droughts are beginning to reduce the productivity and quality of agricultural yields. This research aims to explore the impact of climate change on agricultural production, with a focus on the food crop agriculture sector in Indonesia. Through a literature review from various sources, it was found that climate change causes shifts in planting seasons, decreases in crop yields, and increases in pest and plant disease attacks. These factors also reduce farmers' income and worsen food security. To reduce these negative impacts, it is important for Indonesia to implement policies that support sustainable agricultural practices, the application of environmentally friendly technologies, and provide accurate information to farmers.